2011
DOI: 10.1111/j.1369-1600.2011.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Addictive potential of modafinil and cross‐sensitization with cocaine: a pre‐clinical study

Abstract: Repeated or even a single exposure to drugs of abuse can lead to persistent locomotor sensitization, which is the result of an abundance of neuroplastic changes occurring within the circuitry involved in motivational behavior and is thought to play a key role in certain aspects of drug addiction. There is substantial controversy about the addictive potential of modafinil, a wake-promoting drug used to treat narcolepsy that is increasingly being used as a cognitive enhancer and has been proposed as a pharmacoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 53 publications
7
39
1
Order By: Relevance
“…For instance, cross-sensitization between COC and AMP (Bonate et al, 1997) has been reported, strongly suggesting common neurobiological mechanisms (Wuo-Silva et al, 2011). Of note, in the present study, there was a potentiation of cross-sensitization between AMP and COC (two drugs that distinctly modulate the dopaminergic system) in prenatally Poly(I:C)-treated mice, strengthening the role of dopaminergic system in the behavioral modifications promoted by Poly(I:C) administration.…”
Section: Accepted Manuscriptmentioning
confidence: 57%
See 1 more Smart Citation
“…For instance, cross-sensitization between COC and AMP (Bonate et al, 1997) has been reported, strongly suggesting common neurobiological mechanisms (Wuo-Silva et al, 2011). Of note, in the present study, there was a potentiation of cross-sensitization between AMP and COC (two drugs that distinctly modulate the dopaminergic system) in prenatally Poly(I:C)-treated mice, strengthening the role of dopaminergic system in the behavioral modifications promoted by Poly(I:C) administration.…”
Section: Accepted Manuscriptmentioning
confidence: 57%
“…These effects have been attributed to stimulation of dopamine release in mesolimbic dopaminergic system (Alcaro et al, 2007;Wise and Bozarth, 1987;Wuo-Silva et al, 2011). It has been extensively shown that repeated administration of psychostimulants enhances their stimulatory effect on the activity of mesoaccumbens system (Vezina, 2004), leading to a sensitization of the locomotor stimulatory effect (Robinson and Becker, 1986;Costa et al,2007;Marinho et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…There is now evidence that explicitly supports their view. For instance, modafinil has recently been shown to be addictive in animals (Wuo-Silva et al 2011), and several studies show that it might also be addictive in healthy humans (Volkow et al 2009). Indeed, it has been placed under Schedule IV of the Controlled Substances Act and classified as having the potential to lead to psychological and physiological dependency (Cephalon 2009; Food and Drug Administration 2010).…”
Section: Modafinil Has the Potential For Addictionmentioning
confidence: 97%
“…Indeed, two independent studies have contradicted earlier reports and indicated that modafinil can indeed produce place preference at high doses (64–300 mg/kg) in mice [22,23]. Furthermore, locomotor sensitization to modafinil has also been observed in mice [23,24]. Together, these recent findings indicate that modafinil, even when taken alone, may have addictive potential.…”
Section: Introductionmentioning
confidence: 94%
“…Modafinil increases dopamine activity in the accumbens [1720] and human patients “self-administer” the drug in a “modified progressive ratio procedure” [21]. Indeed, two independent studies have contradicted earlier reports and indicated that modafinil can indeed produce place preference at high doses (64–300 mg/kg) in mice [22,23]. Furthermore, locomotor sensitization to modafinil has also been observed in mice [23,24].…”
Section: Introductionmentioning
confidence: 99%